Biological Characteristics of Five Wood-Rot Fungi in Sand-buried Sections of Salix Psammophila - Duan Xiaoting; Gao Yong; Liang Yumei; Wang Ruidong; Zhao Chen; Guo Xin (Shuitu baochi tongbao)
[Objective] The influence of culture conditions (carbon source, nitrogen source, and pH value) on the growth of wood-rot fungi was analyzed in order to provide a theoretical basis for prolonging the service period of Salix psammophila sand barriers. [Methods] Trichoderma citrinovicide, Xylogone sphaerospora, Trichoderma harzianum, Trichoderma koningiopsis, and Aspergillus niger in sand-buried sections of S. psammophila were the five fungi species used as research objects. The growth rate and biomass of mycelium under different culture conditions (solid and liquid) were investigated to determine the optimal growth conditions for each fungi species. [Results] ① Under solid culture conditions, T. citrinoviride, X. sphaerospora, T. harzianum, and A. niger grew fastest when glucose was used as the carbon source, and their growth rates were 12.97, 8.56, 13.25, and 5.22 mm/d, respectively; The best nitrogen source for T. citrinoviride was ammonium sulfate, and the growth rate was 13.06 mm/d. The best nitrogen source for X. sphaerospora, T. harzianum, and T. koningiopsis was peptone, and their growth rates were 9.44, 13.17, and 8.78 mm/d, respectively; The optimum pH value for the five species of wood-rot fungi was between 5 and 7. ② Under liquid culture conditions, glucose was the best carbon source for the five species of wood-rot fungi, and the biomass values per 100 ml of culture medium reached 446.67, 454.67, 728.67, 687.67, and 713.00 mg, respectively. The most suitable nitrogen source for T. citrinoviride, X. sphaerospora, T. harzianum, and T. koningiopsis was peptone. The biomass of A. niger was 610.00 mg when ammonium chloride was used as the nitrogen source. The biomass of the five species of wood-rot fungi was large in the pH value range from 5 to 7. [Conclusion] Under solid and liquid conditions, the most suitable carbon source for T. citrinoviride, X. sphaerospora, and T. harzianum is glucose, the most suitable nitrogen source is peptone, and the pH value is between 5 and 6. Under the liquid culture condition, the most suitable carbon source for T. koningiopsis is glucose, the most suitable nitrogen source is peptone, and the pH value is between 5 and 6. Under the liquid culture condition, the most suitable carbon source for A. niger is glucose, the most suitable nitrogen source is ammonium chloride, and the pH value is between 5 and 6.